Pengaruh Pemberian Vitamin E Dengan Dosis Yang Berbeda Pada Pakan Terhadap Pemijahan Lobster Air Tawar (Cherax quadricarinatus) - Nusi, Vina adelia; Juliana, Juliana; Suherman, Sutianto P. (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2024)
Freshwater lobster (Cherax quadricarinatus) is a type of lobster that has the potential for developed as a cultured organism. The problem that often occurs is the low number of freshwater lobster production due to the relatively long reproductive time. Vitamin E is a nutrient that plays a role in improving the spawning process in animals. This research aims to determine the effect of vitamin E to artificial feed at different doses on spawning. The test animals used were 16 female freshwater lobsters measuring 4 inches, aged 6 months, with an average weight of 30-55 grams. The research was conducted over 60 days using an experimental method with a completely randomized design (CRD) consisting of 4 treatments with 4 replications each. Treatment A was without vitamin E, Treatment B had 250 mg/kg of feed, Treatment C had 450 mg/kg of feed, and Treatment D had 650 mg/kg of feed The results showed that the levels of gonad maturity, fecundity, degree of fertilization, egg hatchability, and survival rate were not significantly different among treatments. However, Treatment C yielded the best results, with a gonad maturity level of 10.60%, fecundity of 281.53 eggs, a fertilization rate of 8.59%, a hatchability rate of 62.50%, and a survival rate of 100%. Data analysis was conducted using analysis of variance (ANOVA) at a 95% confidence level. The results indicate that the addition of vitamin E to feed at different doses does not significantly affect the spawning of freshwater lobsters.